EVALUASI PELAKSANAAN TEACHING FACTORY DALAM MENINGKATKAN KETERAMPILAN DAN MOTIVASI BERWIRAUSAHA SISWA SMK DI KOTA MAKASSAR - Harianti; Muhammad Yahya; andi muhammad irfan (UNM Journal of Technology and Vocational, 2022)
This study aims to discover (1) the implementation of teaching factory at SMK in Makassar city based on the context, input, and process components and (2) the implementation of teaching factory at SMK in Makassar city in terms of product components based on the students' entrepreneurial skills and motivation. The study was conducted with an evaluation approach with a context, input, process, product model. The respondents of the study were educators and students at SMK with the total of 42people. Data collection techniques employed document studies, observations, and questionnaires. Data were analyzed descriptively by percentage. The results of the study reveal that the overall teachingfactory implementation of CIPP components is in very good category, which includes: the context component is in "very good" category, the input component is in "very good" category, the process component is in "very good" category, and the product component is in "very good" category. Furthermore, the implementation of the teaching factory is effectively used to improve the entrepreneurial skills and motivation of SMK students in Makassar city.